KARAKTERISTIK KEMISKINAN DI KOTA BENGKULU TAHUN 2015 – 2019 - Barika Barika; Yusnida Yusnida (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to analyze The Poverty Characteristic in Bengkulu City. We use descriptive qualitative method according mixing data from Central Bureau of Statistics (BPS) and The National Team for the Acceleration of Poverty Reduction (TNP2K). This study found that the percentage of poor people in the city of Bengkulu during 2015-2019 decreased, as well as the poverty depth index (P1) and the poverty severity index (P2). The poverty line shows an increasing trend and in 2019 it will be IDR 660,442 per capita per month. The Selebar sub-district has the largest distribution of the number of poor people in the city of Bengkulu is in. The largest number of children attending school in the poor population group in a wide district, and the number of children attending school is greater than those who do not. The number of people over 15 years of age who do not work is more than those who work. The largest housing ownership status is self-owned with the main source of lighting from PLN electricity.